Mediating effect of collaborative learning on learning management system usage and academic performance - Tian, Yang; Chan, Tak Jie; Syed Zainudin, Sharifah Sofiah; Mohd Jalis, Farhana Muslim (Grand Canyon University, 2025)
This study aims to identify the mediating effect of collaborative learning on the relationship between Learning Management System (LMS) usage and academic performance among undergraduate students in a public university through the constructivism theory. The study employed a purposive sampling survey method, and 381 valid respondents were collected. Data analysis was conducted based on the Partial Least Square Structural Equation Model (PLS-SEM). As a result, LMS usage positively impacts the academic performance of the students. Besides, LMS usage significantly impacts collaborative learning, and collaborative learning positively influences academic performance. Lastly, collaborative learning was found to exert a partial mediating effect on the relationship between LMS usage and academic performance. This research contributes to the existing literature and illustrates that collaborative learning through LMS can enrich learning activities and promote group discussions. Conclusion, implications, and avenues for future research are discussed.